1994
DOI: 10.1063/1.356306
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of TiO2 anatase thin films

Abstract: Electrical and optical spectroscopic studies of TiO2 anatase thin films deposited by sputtering show that the metastable phase anatase differs in electronic properties from the well-known, stable phase rutile. Resistivity and Hall-effect measurements reveal an insulator–metal transition in a donor band in anatase thin films with high donor concentrations. Such a transition is not observed in rutile thin films with similar donor concentrations. This indicates a larger effective Bohr radius of donor electrons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

92
1,041
12
15

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,735 publications
(1,160 citation statements)
references
References 28 publications
92
1,041
12
15
Order By: Relevance
“…4a. It is revealed that these loops show antiferromagnetic behavior which may be due to the presence of hematite phase [12]. This phase is also confirmed by XRD micrographs.…”
Section: Vsm Analysissupporting
confidence: 60%
“…4a. It is revealed that these loops show antiferromagnetic behavior which may be due to the presence of hematite phase [12]. This phase is also confirmed by XRD micrographs.…”
Section: Vsm Analysissupporting
confidence: 60%
“…The obtained band gap estimate for the pure TiO2 film of 3.25 eV is in accord with the literature value of 3.2 eV for anatase TiO2. 31 The TiO2 band gap was found to blue-shift in the superlattice films with decreasing superlattice period with an onset between periods of 1:20 (0.96 nm) and 1:40 (1.9 nm) 13 finally reaching 3.75 eV for the m=0 hybrid. The blue-shift is probably due to quantum confinement of electrons with decreasing TiO2 domain size in analogy to nanocrystalline materials in which a decrease in grain size leads to an increase in the band gap.…”
Section: Resultsmentioning
confidence: 94%
“…Values of the optical band gap Eo are comparable to those previously reported for Ti02 films. Values of Eo are found to be 3.2eV and 3.0eV for reactively triode sputtered Ti@ films in anatase and rutile, respectively [22]. Leinen et al [23] have recently reported a band gap in the range of 3.3-3.42eV for induced chemical vapour deposited anatase films.…”
Section: Resultsmentioning
confidence: 99%